1999
DOI: 10.1111/j.1752-1688.1999.tb04239.x
|View full text |Cite
|
Sign up to set email alerts
|

SPATIAL AND TEMPORAL ANALYSIS OF AGRICULTURAL WATER REQUIREMENTS IN THE GULF COAST OF THE UNITED STATES1

Abstract: Competition for water resources is becoming an increasingly important issue in the southeastern U.S. The potential impacts of future precipitation and runoff estimated by a transient global climate model (HADCM2) on competing water resources in the Southeast has been conducted. Issues of agricultural management, irrigation water withdrawals, and water quality were studied over three time periods: 1974–1993, 2020–2039, and 2080–2099 in five water basins identified previously as exhibiting water‐related problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…Efforts have been made to apply the model in agricultural watersheds to simulate plant growth, irrigation management, impact of climate change on irrigation, effects of irrigation on runoff, and interactions among climate, crops, soils, and water (Ritschard et al, 1999;Sophocleous and Perkins, 1999;Gosain et al, 2005;Luo et al, 2008). However, simulating the complicated irrigation canal network of the agricultural watersheds often goes beyond capacities of the current standard version SWAT model.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to apply the model in agricultural watersheds to simulate plant growth, irrigation management, impact of climate change on irrigation, effects of irrigation on runoff, and interactions among climate, crops, soils, and water (Ritschard et al, 1999;Sophocleous and Perkins, 1999;Gosain et al, 2005;Luo et al, 2008). However, simulating the complicated irrigation canal network of the agricultural watersheds often goes beyond capacities of the current standard version SWAT model.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the regional assessment studies underway in the United States are employing the Vegetationl Ecosystem Modeling and Analysis Project (VEMAP) climatic database (Kittel et at., 1995). Portions of the VEMAP database have been used in several studies in regional assessments (see and Ritschard et at., 1999). The VEMAP data sets contain daily and monthly climate data (Tmax, Tmin, precip., solar rad.)…”
Section: Data Sourcesmentioning
confidence: 99%
“…Studies (Kittel et at., 1995) have indicated that probable climate change scenarios would include temporal variability of temperature, precipitation, radiation and vegetation (e.g., LAI). Changes in these variables will certainly lead to changes in hydrologic processes such as ET (Ritschard et at., 1999). SWAT allows explicit inclusion of all of the cited atmospheric variables and employs these variables to simulate the relevant hydrologic processes.…”
Section: Routing Of Hydrograpbs To Watershed Outletmentioning
confidence: 99%
See 1 more Smart Citation
“…SWAT, as a physically-based, spatially distributed hydrological model, has been widely used to simulate the ecological, hydrological, and environmental processes under a range of climate and management conditions throughout the world since 1993 (as indicated by nearly 150 publications documented by Gassman et al, 2007). For example, SWAT was used for assessing the impact of irrigation diversion on river flow in the Midwest of the US (e.g., Ritschard et al, 1999;Hatch et al, 1999;Sophocleous and Perkins, 2000;Bosch et al, 2004;Santhi et al, 2005;Behera and Panda, 2006), for simulating climate change scenarios and their related impacts (Edmonds and Rosenberg, 2005;Izaurralde et al, 2005), and for modeling sediment or nutrient yield (Haggard et al, 2005;Lenhart et al, 2005). The wide applications of SWAT are probably attributed to the comprehensive considerations of hydrologic, biological, and environmental processes, incorporation of management scenarios, availability of parameter databases, and its robustness, flexibility, and user friendliness.…”
Section: Introductionmentioning
confidence: 99%